Adult small bowel Dieulafoy lesion. Issue 914 (1st December 2001) - Fox, A; Ravi, K; Leeder, P C; Britton, B J; Warren, B F
Abstract : A 47 year old woman presented with melaena and haemodynamic instability. Preliminary investigations failed to locate the source of bleeding. At laparotomy an arteriovenous malformation was identified in the distal ileum. Histology revealed this to be of the Dieulafoy type. This is the first published case of a histologically proved ileal Dieulafoy lesion in an adult.